The Reflection of the Olfactory Traditions of the Second Half of the 19th Century in the Work of Fyodor Dostoevsky - Olga A. Dekhanova (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2021)
The rapid development of natural sciences at the beginning of the 19th century led to the creation of new sanitary and hygienic standards. The attention of the public opinion was now turned to keeping the body and clothing perfectly clean as a way of preventing diseases. New sanitary and hygienic regulations now prescribed not to mask unpleasant bodily odors with aromatic means, but to keep the body and clothing clean, which was regarded as a guarantee of bodily health. The popularization of new scientific discoveries through articles in public newspapers and magazines prepared the public consciousness for a new perception of the smells of everyday life, and the fiction, responding to the discussed social phenomena, fixed new cultural standards in the minds of readers. In this paper, we consider some of the new olfactory criteria used for evaluating characters or behavior patterns in works of fiction written in the second half of the 19th century, as well as their patterns and peculiarities in Dostoevsky’s oeuvre.